Efficacy of Yogasana and Pranayama in Viriperukkanaalam - case study - Jenany, T.; Thanuraj, P.; Sounthararajan, K. (University of Jaffna, 2018)
Yoga is one of the most extraordinary spiritual sciences that mankind has ever discovered. "Viriperukkanaalam" is a disease which become dialated, elongated and tortuous veins and most commonly affected in legs and feet. Patients may seek treatment because of the severe pain and unpleasant appearance. Various types of treatment are mentioned in Siddha, Ayurveda, traditional and allopathic Medicine several method of limb bandaging, exercises, injection and surgery are reported to reduce the condition with varying success rates. A case study was carried out to identify the efficacy of yogasana and pranayama for Viriperukkanaalam. A case of 63year old female patient came to the yoga clinic of the Out Patient Department of Rural Siddha Hospital, Mulliyawalai with complaints of varicosity and difficult to walk due to pain and swelling. The case was diagnosed Grade IV Superficial Femoral Incompetence (SFI), Incompetent perforators towards Superficial Femoral vein (SFV) by western physician. Selected yogasana and pranayama were carried out for 3months. The patient was completely relived from "Viriperukkanaalam" and it's all symptoms in 8 weeks. According to the above study, it shows that there is a remarkable recovery in patients subjected to yogasana and pranayama. Thus it can be suggested that the Yogasana and Pranayama can be an effective management of "Viriperukkanaalam”.
Keywords: Viriperukkanaalam; Yoga; Yogasana; Pranayama; Varicose vein